Corrosion Analysis On Internal Plastic Coating Drill Pipe 5 Inch 19.50 PPF Grade G-105 - Ario Oktora; Eka Sri Yusmartini; Muhammad Faizal (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
In the oil, gas and geothermal drilling industry, the use of a drill pipe is vital for its use as an addition to the length of the drilling depth. Another function of the drill pipe is to channel high pressure drilling mud (drilling fluid / fluid) to the drill bit. During the drill pipe operation, several problems were encountered, such as broken, bent, and leaking or wash-out drill pipes. This is very detrimental to the company because the time to replace a new drill pipe will take a long time, and will disrupt the drilling program which will result in high drilling operational costs. This study analyzes the corrosion of the drill pipe which can cause damage to the drill pipe. The analysis on the drill pipe includes analysis of thickness, corrosion rate, remaining life, internal plastic coating damage, and SEM. The results show that the storage and use of drill pipes greatly affect the conductivity of the drill pipe.